Development of a Financial Management Application for Boarding Students Using the Waterfall Method An Effective Solution for Managing Budgets and Expenses - Muhammad, Nibras Faiq; Andhini, Asmara (IC-ITECHS, 2024)
Financial management is a considerable difficulty for students residing in boarding homes, who often possess restricted revenue sources and diverse expenditure requirements. An extravagant lifestyle coupled with inadequate financial literacy frequently results in students encountering difficulties with budgeting and experiencing financial crises at month’s end. This study seeks to create a web-based financial management tool employing the Waterfall methodology, intended to assist students in documenting income and expenditures, managing budgets, and enhancing their financial literacy. The Waterfall technique is methodically executed through the phases of requirements analysis, design utilising UML, implementation employing tools such as Vscode and MySQL, and testing to verify the application's operation. This program has transaction recording capabilities, financial reporting, and profile management, enabling students to efficiently track cash flow and assess spending habits. The research findings indicate that this application assists students residing in boarding homes in managing their funds more systematically, mitigates the danger of extravagance, and enhances awareness of the significance of effective financial management. This application aims to enhance students' independence in money management and facilitate their preparation for a secure financial future